What is the Currency of Being Good? Aligning Objective and Subjective CSR Agreements for Shaping Sustainable Governance in Socially Responsible Business Organizations - Katarzyna KLIMKIEWICZ; Victor OLTRA (Communications of International Proceedings, 2025)
Drawing upon legitimacy theory, social contract theory, social identity theory, and organizational identity theory, in this paper, we discuss different approaches to Corporate Social Responsibility (CSR) as an extended governance model constructed and shared among individuals, both inside and outside organizations. Delving into the underlying mechanisms that drive organizational and individual responses towards CSR, we aim at providing a framework for understanding the linkages between socially constructed CSR, its incorporation into the governance model, as well as cognitive and behavioural responses towards those CSR approaches adopted by individuals. The core argument supporting the rationale of this investigation is that the effectiveness of CSR approaches depend on the alignment of the two contracts: (1) between the organization and the society (objective agreement), and (2) between the individuals and the organization (subjective agreement). The alignment of these contracts remains a matter of confrontation between the outcomes resulting from the specific CSR approaches adopted by the organization and how individuals perceive these outcomes. By analyzing the core features of three types of CSR as extended governance models – compliance, relational and sustainable organization models – we frame possible directions for structuring the discussion on the impacts CSR/CS might have on individual perceptions and behaviours (e.g., employees, customers, managers).
Keywords: Corporate Social Responsibility; social contract; psychological contract; sustainable corporate governance model